2020
DOI: 10.1186/s12865-020-00377-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of TIM-3 expression with glucose metabolism in Jurkat T cells

Abstract: Background T cell activation is associated with increase in glycolysis and glutaminolysis. T cell immunoglobulin and mucin domain containing protein-3 (TIM-3), a T cell surface molecule, downregulates T cell activation and leads to insufficient immunity in cancer and chronic infection. TIM-3 regulates T cell activation possibly through alterations in metabolism; however, the relationship between TIM-3 expression and T cell metabolic changes has not been well studied. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…We have taken this approach in part because of the aforementioned complexity in Tim-3 ligands. Based on previous studies from our group and others, we believe that such overexpression results in enhanced Tim-3 signaling ( Avery et al, 2018 ; Lee et al, 2011 , 2020 ). Indeed, our finding that Treg cells expressing endogenous levels of Tim-3 display a very similar phenotype to the Tim-3 Tg Treg cells supports this assertion.…”
Section: Discussionmentioning
confidence: 80%
“…We have taken this approach in part because of the aforementioned complexity in Tim-3 ligands. Based on previous studies from our group and others, we believe that such overexpression results in enhanced Tim-3 signaling ( Avery et al, 2018 ; Lee et al, 2011 , 2020 ). Indeed, our finding that Treg cells expressing endogenous levels of Tim-3 display a very similar phenotype to the Tim-3 Tg Treg cells supports this assertion.…”
Section: Discussionmentioning
confidence: 80%
“…PD1, TIGIT and TIM3 checkpoint inhibitory receptors can affect the glycolytic metabolism (28)(29)(30), but our results suggested that specific combinations of these receptors might differentially affect glycolysis induction and function of CD8+ T cells from ST-ARTp and LT-ARTp. Supporting this possibility, we observed significant positive correlations between the increase on glycolytic capacities, defined by delta ECAR from basal versus maximum values after TCR activation on CD8+ T cell, and the percentages of single positive TIGIT or TIM3 expression from the total CM or EM cells (Figure 5A-B, upper panels; Supplementary figure 8B-C, upper panels).…”
Section: Combined Blockade Of Checkpoint Inhibitory Receptors and Adm...mentioning
confidence: 58%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted January 16, 2022. ; https://doi.org/10.1101/2022.01.14.476403 doi: bioRxiv preprint process involving expression of multiple checkpoint inhibitory receptors that drive the transition, survival and function of distinct memory cell subsets (24,26,27). Importantly, expression of checkpoint inhibitory receptors such as PD1, TIGIT and TIM3 in T cells is also associated with deregulated glucose metabolism (28)(29)(30), which could lead to impaired effector function and longevity of HIV-1 specific CD8+ T cells (31)(32)(33). In fact, compromise of metabolic fitness has been reported in PLWH and suggested to affect CD8+ T cell function (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CTLA-4 engagement on T cell surface dampens the activation of PI3K/Akt/mTOR [ 105 ], and therefore reduces glycolysis. Knock-out of TIM-3 in an in vitro T cell model reduces glucose uptake and glycolysis [ 106 ]. Overall, given the connections mentioned above between metabolism and migration in T cells, the effects of these inhibitory co-receptors on T-cell motility described above may also depend on the concomitant alteration of T-cell metabolism.…”
Section: Metabolism and T-cell Migration Within Tumorsmentioning
confidence: 99%